Beta diversity of pelagic assemblages at fish aggregating devices in the open ocean. Issue 2 (2nd April 2020) - Forget, F; Dagorn, L; Mérigot, B; Gaertner, JC; Robinson, J; Cowley, PD; Adam, MS; Rilwan, Y; Koonjul, M; Mangar, V; Taquet, M; Ménard, F
Abstract : Owing to difficulties in accessing the vast open ocean, the beta (β) diversity of pelagic fish assemblages remains poorly studied. We investigated the relationship between assemblage similarity and geographical distance between anchored fish aggregating devices (FADs), sampled by standardised underwater visual censuses in three anchored FAD arrays in the Indian Ocean—at the Maldives, the Seychelles and Mauritius. The use of two complementary indices of β-diversity, based on presence/absence data (Jaccard similarity coefficient) and abundance data (Bray–Curtis index), revealed that geographical distance between sampling sites (from 4 to 257 km) appeared to have no effect on the similarity of fish assemblages associated with FADs within each array. The results of this preliminary study question the generalisation of the paradigm of an increase in β-diversity with geographic distance to the open-ocean fish community. Large-scale studies using a variety of datasets should be conducted to further investigate patterns of β-diversity in the open ocean.